2013
DOI: 10.1007/978-3-642-41181-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Local Intrinsic Dimensionality Based Features for Clustering

Abstract: One of the fundamental tasks of unsupervised learning is dataset clustering, to partition the input dataset into clusters composed by somehow "similar" objects that "differ" from the objects belonging to other classes. To this end, in this paper we assume that the different clusters are drawn from different, possibly intersecting, geometrical structures represented by manifolds embedded into a possibly higher dimensional space. Under these assumptions, and considering that each manifold is typified by a geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The idea that ID may vary in the same data is not new. In fact, many works have discussed the possibility of a variable ID and developed methods to estimate multiple IDs [7][8][9][10][11][12][13][14][15][16][17][18][20][21][22] . Our method builds on these previous contributions but is designed with the specific goal of overcoming technical limitations of other available approaches and make ID-based segmentation a general-purpose tool.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea that ID may vary in the same data is not new. In fact, many works have discussed the possibility of a variable ID and developed methods to estimate multiple IDs [7][8][9][10][11][12][13][14][15][16][17][18][20][21][22] . Our method builds on these previous contributions but is designed with the specific goal of overcoming technical limitations of other available approaches and make ID-based segmentation a general-purpose tool.…”
Section: Discussionmentioning
confidence: 99%
“…Let x = {x i } be i.i.d samples from a density ρ(x) with support on the union of K manifolds with varying dimensions. This multi-manifold framework is common with many previous works investigating heterogeneous dimension in a dataset [8][9][10][11][14][15][16][18][19][20]24,25 . Formally, let ρ(x) = K k=1 p k ρ k (x) where each ρ k (x) has support on a manifold of dimension d k and p .…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, in [17] the authors mark that, in order to balance a classifier generalization ability and its empirical error, the complexity of the classification model should also be related to the id of the available dataset. Furthermore, since complex objects can be considered as structures composed by multiple manifolds that must be clustered to be processed separately, the knowledge of the local ids characterizing the considered object is fundamental to obtain a proper clustering [18].…”
Section: Application Domainsmentioning
confidence: 99%
“…Local intrinsic dimensionality focuses on the intrinsic dimension of a particular query point and has been used in a range of applications. These include modeling deformation in granular materials [ 20 , 21 ], climate science [ 22 , 23 ], dimension reduction via local PCA [ 24 ], similarity search [ 25 ], clustering [ 26 ], outlier detection [ 27 ], statistical manifold learning [ 28 ], adversarial example detection [ 29 ], adversarial nearest neighbor characterization [ 30 , 31 ] and deep learning understanding [ 32 , 33 ]. In deep learning, it has been shown that adversarial examples are associated with high LID estimates, a characteristic that can be leveraged to build accurate adversarial example detectors [ 29 ].…”
Section: Related Workmentioning
confidence: 99%